Tibiotalocalcaneal (TTC) arthrodesis with reverse PHILOS plate and medial cannulated screws with lateral approach - Fan, Jian (BMC Musculoskelet Disord, 2017)
BACKGROUND: Tibiotalocalcaneal arthrodesis is most common and effective surgical treatment for severe hindfoot pathology, but the fusion rate is often lower than the ordinary tibiotalar arthrodesis because of the more serious joint disease associated with obvious deformity and osteoporosis. Recent literature describe tibiotalocalcaneal arthrodesis with reverse PHILOS plate with good clinical outcome result, though some patients non-union, due to eccentric force of the plate may be hidden. The purpose of this study was to evaluate clinical outcome of the lateral approach for tibiotalocalcaneal (TTC) arthrodesis with reverse PHILOS Plate and medial cannulated screw. METHODS: Between Jun, 2013 to April, 2015 12 patient with hindfoot pathology had TTC arthrodesis with a reverse PHILOS plate with medial cannulated screw through a lateral approach with resection of the distal fibula and bone graft. Perioperatively observe for wound and neurovascular status. Patients were follow-up from post-operative 1, 3, 6 and12 months, to observation of wound healing, ankle pain, subtalar Joint Fusion, internal fixation and ankle function. Ankle function were scored according to the American Orthopaedic Foot and Ankle Society(AOFAS) Ankle-Hindfoot Scale system. RESULTS: Twelve ankle fusion all patient follow-up, with mean time to surgery 18.6 months (12-36 month). No cases infection and issue necrosis; one patient complaint of lateral foot numbness we observe and follow-up was spontaneously recovery after 3 months. After 3 months of operation, no obvious pain of ankle joint and internal fixations loose were found. Almost fusion and good axial alignment of TTC joint also were found by X-ray and CT examination. After final fellow-up of each case, no case complain of pain of ankle joint, good fusion and axial alignment of TTC joint were also all found through Terminology. The mean American Orthopaedic Foot and Ankle society (AOFAS) score average was 77.5. CONCLUSION: TTC arthrodesis with reverse PHILOS Plate and medial cannulated screw have advantages of clear incision, effective bone orthopaedic and graft fully secure, stable internal fixation, high fusion rate and less complications, can effectively correct deformities, alleviate hindfoot pain and improve function, and is an effective method of treatment of after severe hindfoot disease. TRIAL REGISTRATION: This trial is registered on ClinicalTrials.gov with reference number: ID: NCT02977910. Registered 26 Nov 2016, retrospectively registered.